Hepatoprotective and antioxidant effects of alcesefoliside from Astragalus monspessulanus - Magdalena Kondeva-Burdina; Rumyana Simeonova; Aleksandar Shkondrov; Ilina Krasteva; Georgi Popov; Vassil Manov (Universidade de São Paulo, 2022)
Abstract The hepatoprotective potential of alcesefoliside (AF) from Astragalus monspessulanus was investigated. Iron sulphate/ascorbic acid (Fe2+/AA) lipid peroxidation was induced in rat liver microsomes and pre-incubated with AF and silybin (100, 10 and 1 µmol). Pronounced effects were observed in 100 µmol. In vivo experiments were carried out on rats, challenged orally with carbon tetrachloride (CCl4) alone and after pre-treatment and followed by curative treatment with AF (10 mg/kg). The activity of the serum and antioxidant enzymes, together with reduced glutathione (GSH) levels and malonedialdehyde (MDA) quantity were measured. Microsomal incubation with Fe2+/AA increased MDA production. The pre-incubation with AF reduced the formation of MDA, comparable to silybin. These findings were supported by the in vivo study where CCl4-induced liver damage was discerned by significant increase in serum enzymes and in MDA production as well as by GSH depletion and reduced antioxidant enzymes activity. The AF pre-treatment and consecutive curative treatment normalizes the activity of the serum and antioxidant enzymes alike, as well as the levels of GSH and MDA. Histological examination of AF-treated livers showed a decrease in the abnormal accumulation of lipids in hepatocytes as well as reduced alterative changes in their structure in a model of CCl4-induced toxicity.